Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Perataan Laba - Novela suci pratika; Suhesti Ningsih; Sri Laksmi Pardanawati (Nur Science Institute, 2022)
The purpose of this study was to determine the effect of profitability, leverage, and firm size on income smoothing either simultaneously or partially. In this study, using primary data with descriptive analysis method, classical assumption test and hypothesis testing using multiple linear regression analysis. Simultaneous test results can be seen from the calculated F value 0.289 < F table 2.69. Based on the results of hypothesis testing, it is obtained that profitability has a positive effect on income smoothing, this is indicated by the results of the t test of 0.033 <0.05. While the results of hypothesis testing are obtained that leverage has no effect on income smoothing, this is indicated by the results of the t-test of 0.072 > 0.05, and based on the results of hypothesis testing, it is obtained that firm size has an effect on income smoothing, this is indicated by the results of the t-test of 0.042 < 0 ,05. The magnitude of the influence of the variables of profitability, leverage, and company size simultaneously affects income smoothing by 46.6%.